Sign language-based virtual reality supports motor coordination learning in deaf children development - Fahmil Haris; Ilham Ilham; Nugroho Susanto; Raihan Alfarobi; Fauzan Aulia; Nessya Fitryona; Uswatul Hakim; Vlad Adrian Geantă; Henny Yustisia; Atika Ulya Akmal (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2026)
This study developed and validated sign language-based Virtual Reality (VR) learning media for improving motor coordination in children with hearing impairments. A Research and Development design integrating the Borg and Gall model with the ADDIE framework was employed. Nine experts evaluated the media using Aiken's V and Cronbach's Alpha, followed by Focus Group Discussions for product refinement. The media demonstrated high content validity with an overall Aiken's V coefficient of 0.894, including content (0.889), design (0.903), and usability (0.891). Instrument reliability was also high (Cronbach's Alpha = 0.832), indicating strong internal consistency. The developed VR media demonstrated satisfactory validity and reliability as a learning medium for motor coordination. Further experimental studies involving deaf children are required to verify its effectiveness in improving motor skills under authentic educational settings.